El problema social del indio (1923 y 1971) - Miguel Ángel Asturias (Les Cahiers ALHIM)
This leading Guatemalan personality has been one of the first pro-Indian Intellectual of his country. In his thesis “El problema social del indio” at the beginnings of the 1920s, he analysed and offered solutions to the Maya people’s problems. At the beginning of the 1970’s decade he amended substantially some of his proposals.